Commodity Bundling and the Burden of Monopoly - Adams, William James; Yellen, Janet L. (Quarterly Journal of Economics, 1976)
I. Introduction, 475.—II. The model: positive properties, 477.—III. The model: normative properties, 490.—IV. Implications and conclusion, 495.